(untitled) (Fenestella. Inside Medieval Art, 2020)
The article aims to briefly observe stylistic features of most of the ensembles and single works of Byzantine monumental painting created c.1100, completing information brought forward in previous publications with data, which only recently have become widely known to the scientific community. At the turn of the eleventh century the most important role belonged to a classical artistic tradition associated with Constantinopolitan artists, who sometimes – to judge from the quality of the monuments – came to work in the provinces (Kiev, Cyprus). It is represented in a series of illuminated manuscripts but only in a few ensembles of mosaics and frescoes. On the base of the “ascetic” style of 1030s-1040s a few groups of monuments took shape, which not always differ greatly from each other in style but seem to develop one or another of its features (spiritual strength and vigour of images, uniform rendering of figures, linear stylization, transformation of substance with light etc.). The expressive trend was probably at the beginning of its formation to reach the height by the end of the twelfth century. In whole, the art of the period c. 1100 is characterized by more individual and gentle treatment of images and their growing psychological insight.